2008
DOI: 10.1007/s00468-008-0290-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro plant regeneration from seedling explants of Stereospermum personatum D.C.: a medicinal tree

Abstract: Padar (Stereospermum personatum, family Bignoniaceae) is a well-known medicinal tree. Its complete regeneration occurred through shoot bud culture in vitro. The seeds germinated sequentially on plastic trays and polyethylene bags for 21 days served as explants source. Nodal segments from the seedlings were established on MS medium supplemented with 4.44 lM BA, in which 86.6% nodes showed shoot bud elongation. Then, nodal segments from the developed shoots were cultured on MS medium with several BA concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 14 publications
(11 reference statements)
2
22
0
Order By: Relevance
“…In the present study, shoot tip and nodal segments obtained from two year old plants were used as explants. Better plant regeneration from node of young trees was also reported in Oroxylum (Dalal and Rai 2004), Boswellia ovalifoliolata (Chandrasekhar et al 2005), Pterocarpus santalinus (Rajeswari and Paliwal 2006), Stereospermum personatum (Shukla et al 2008). Browning of explants due to exudation of phenolics has been reported as a serious problem in establishing axenic cultures of tree species (Krishna and Singh 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, shoot tip and nodal segments obtained from two year old plants were used as explants. Better plant regeneration from node of young trees was also reported in Oroxylum (Dalal and Rai 2004), Boswellia ovalifoliolata (Chandrasekhar et al 2005), Pterocarpus santalinus (Rajeswari and Paliwal 2006), Stereospermum personatum (Shukla et al 2008). Browning of explants due to exudation of phenolics has been reported as a serious problem in establishing axenic cultures of tree species (Krishna and Singh 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MS medium supplemented with 4.44 μM BAP was found to be the most suitable medium for establishment of nodal explants of S. suaveolens. In earlier studies also MS medium was found suitable for in vitro establishment of explants from hardwood trees such as Terminalia arjuna Roxb [11], Tectona grandis [12], Gmelina arborea [13], woody climber Bauhinia vahlii [14] and Stereospermum personatum [15]. Shoot bud elongation occurred when nodes were placed on MS medium supplemented with 0.0, 0.04, 0.44 or 4.44 µM BAP [16].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, IBA has been observed to induce strong rooting response over IAA or NAA and has been extensively used to promote rooting in a wide range of tree species such as Myrtus communis (Ruffoni et al 1994;Scarpa et al 2000), Pistacia vera (Onay 2000), Terminalia arjuna (Pandey and Jaiswal 2002;Pandey et al 2006), Terminalia chebula (Shyamkumar 2003), Kigelia pinnata (Thomas and Puthur 2004), Stereospermum personatum (Shukla et al 2009), Semecar-pus anacardium (Panda and Hazra 2010), and Sapindus trifoliatus (Asthana et al 2011). Moreover, this group of plant hormone is readily and easily available commercially worldwide (Epstein and Ludwig-Miller 1993).…”
Section: Rooting Of In Vitro-regenerated Shootsmentioning
confidence: 97%
“…The increase in shoot number may be due to the suppression of apical dominance during subculture that induced basal dormant meristematic cells to form new shoots (Shukla et al 2009). …”
Section: Subculture Passagesmentioning
confidence: 99%
See 1 more Smart Citation